Role of Transformational Leadership in Building Organizational Competencies Case Study: Genéral Cable Organization, Branch of Biskra, Alger - Chine, Nouel; Chine, Fairouz (The Arab Journal of Administration, 2020)
This study aimed to analyze the influence of strategic leadership in the development of competencies in the organization, case Study of the organization cable industry branch - Genéral cable- Biskra. We chose the transformational leadership style because it is one of strategic leadership styles. We used the questionnaire as a tool for data collection. It was divided into three axes, the first axis deals with the personal and functional characteristics of the study sample, which consisted of 78 individual; while the second axis represents the independent variable in the study which represents the transformational leadership dimensions that consist of four elements (Idealized Influence, Inspirational Motivation, Intellectual Stimulation and Individualized Consideration), the last axis which is the dependent variable, which is represented in organizational competencies construction. To analyze the data, we used statistical package for Social Sciences (SPSS), version number (20). To achieve the aim of study, the main hypothesis was put forward, which were represented in: There is no significant role with statistically significance for the transformational leadership style in building organizational competencies in genéral cable organization, branch of biskra. The following results have been reached: There is a significant moral role between the dimension of intellectual stimulation and organizational competencies in the General Cable Foundation in Biskra. There is a statistically significant moral role between the charisma dimension and organizational competencies in the General Cable Foundation of Biskra. There is a significant moral significance between the motivational dimension and organizational competencies in the General Cable Foundation in Biskra. There is a statistically significant moral role between the dimension of individual interest and organizational competencies in the General Cable Foundation of Biskra. And we have used Step-by-step multiple regression to highlight which of the transformational driving dimensions is most effective compared to other dimensions. The results are as follows: the charisma is the most effective where the effect coefficient was estimated (0.517), and then the individual consideration (0.480) in significant degree (0.000). The remaining dimensions were excluded.